Tournaments of financial analysts - Yin, Huifang (2013)
We argue that financial analysts can be viewed as participants of two tournaments (the “All-star” tournament and the intrafirm tournament) and examine whether analysts are incentivized by the tournament compensation structure. Using data from 1991 to 2007, we find that interim losers are more likely to increase the boldness of their forecasts in the remainder of the tournament period than interim winners. This finding survives several robustness checks and is more pronounced when the interim assessment date is closer to the end of the tournament period, when analysts are inexperienced, and when the market activity is high. In addition, we show that interim losers’ changes in boldness are less informative than interim winners’. Collectively, our findings suggest that viewing financial analysts as participants of tournaments provides a useful framework for understanding analysts’ behavior.